2013
DOI: 10.7453/gahmj.2013.089
|View full text |Cite
|
Sign up to set email alerts
|

Autism: Metabolism, Mitochondria, and the Microbiome

Abstract: New approaches are needed to examine the diverse symptoms and comorbidities of the growing family of neurodevelopmental disorders known as autism spectrum disorder (ASD). ASD originally was thought to be a static, inheritable neurodevelopmental disorder, and our understanding of it is undergoing a major shift. It is emerging as a dynamic system of metabolic and immune anomalies involving many organ systems, including the brain, and environmental exposure. The initial detailed observation and inquiry of patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
140
1
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(148 citation statements)
references
References 97 publications
(224 reference statements)
6
140
1
1
Order By: Relevance
“…98 Despite evidence of anti-inflammatory effects of propionic acid 88 and the recommendation of some researchers that increasing propionic acid synthesis in the colon may be of therapeutic value for metabolic disorders, 99 MacFabe has identified potential neurotoxicity of propionate and studied its possible role in autism. 100 His group found that pathological changes in the brains of animals exposed to intraventricular propionic acid were identical to abnormalities found in the brains of autistic children and adults. Depletion of glutathione and increased markers of oxidative stress accompanied neuroinflammation.…”
Section: Short-chain Fatty Acidsmentioning
confidence: 96%
“…98 Despite evidence of anti-inflammatory effects of propionic acid 88 and the recommendation of some researchers that increasing propionic acid synthesis in the colon may be of therapeutic value for metabolic disorders, 99 MacFabe has identified potential neurotoxicity of propionate and studied its possible role in autism. 100 His group found that pathological changes in the brains of animals exposed to intraventricular propionic acid were identical to abnormalities found in the brains of autistic children and adults. Depletion of glutathione and increased markers of oxidative stress accompanied neuroinflammation.…”
Section: Short-chain Fatty Acidsmentioning
confidence: 96%
“…Health benefits ascribed to these compounds include energy supplementation for colonic epithelium, anti-inflammatory activity, and improved insulin regulation (Segain et al, 2000;Al-Lahham et al, 2010;De Preter et al, 2011). On the other hand, animal model and human epidemiologic studies suggest SCFAs may also induce neurotoxic effects, which might contribute to ASD development (MacFabe, 2013). Some of these detrimental effects are likely due to mitochondrial and epigenetic disruptions (discussed subsequently).…”
Section: Potential Mechanism Microbiota Alterations Lead To Asd and Rmentioning
confidence: 99%
“…The MD observed in autistic cases is thought to be acquired rather than genetic in origin. The SCFAs, especially PPA, which are increased in ASD-associated gut microbes (Clostridia, Desulfovibrio, Sutterella, and Bacteroidetes), might contribute to mitochondrial dysfunction (MacFabe, 2012(MacFabe, , 2013Frye et al, 2013). One mechanism by which the bacterial metabolite PPA may disrupt mitochondria is through alteration of the tricarboxylic acid cycle via conversion of PPA to propionyl-CoA.…”
Section: Potential Mechanism Microbiota Alterations Lead To Asd and Rmentioning
confidence: 99%
“…Propionic acid has bioactive effects on (1) neurotransmitter systems, (2) intracellular acidification and calcium release, (3) fatty acid metabolism, (4) gap junction gating, (5) immune function, and (6) alteration of gene expression [350]. SCFA acts as gut-related environmental signals and are capable of altering host gene expression (including CREBdependent catecholaminergic neurotransmission), partly due to their histone deacetylase inhibitor activity and induced broad alterations in gene expression including neurotransmitter systems (monoaminergic pathways) neuronal cell adhesion molecules, inflammation, oxidative stress, lipid metabolism, and mitochondrial function, all of which have been implicated in ASD [351].…”
Section: Gastrointestinal Dysbiosismentioning
confidence: 99%